(untitled) (Acta Scientiarum. Biological Sciences, 2018)
Campomanesia aurea is a potentially ornamental native fruit shrub. There are no studies on the seed germination capacity and fruit properties of the species. Therefore, the main goal of this paper was to describe the seed germination and the physical and chemical properties of fruits from two C. aurea accession areas. The study was conducted with fruits collected from two native vegetation areas located in the Morro do Osso Natural Park and in the municipality of Barão do Triunfo, Brazil. Physical and chemical analyzes, seed counting and germination tests were performed. Results were submitted to ANOVA and the means were compared by t test at 5% error probability. C. aurea has oblong-shaped fruits weighting around 1.26 g with a high content of vitamin C. Each fruit usually has four intact seeds of which 3% are polyembryonic. Seed germination averaged 93% in 20 days. It is concluded that the C. aurea fruits collected from two different accession areas differ in the concentration of TSS, TSS/TA ratio and vitamin C content, but not physically. Seeds have shown a high germination rate.